Engaging with the crowd - Rotich, Juliana (Technical Centre for Agricultural and Rural Cooperation, 2012)
Crowdsourcing is booming thanks to innovative technology and new developments, and more and more people are picking up on it. But the logistics of setting up crowdsourcing projects in remote rural areas in developing countries is a major challenge